The estimation of the traditionally used yarrow (Achillea millefolium L. Asteraceae) oil extracts with anti-inflamatory potential in topical application. (6th March 2017) - Tadić, Vanja; Arsić, Ivana; Zvezdanović, Jelena; Zugić, Ana; Cvetković, Dragan; Pavkov, Sava
Abstract: Ethnopharmacological relevance: Olive or sunflower oil yarrow extracts have been extensively used against inflammatory disorders and skin wound healing in traditional medicine. Aim of the study: To evaluate oil yarrow extracts traditional use in treatment of topical/dermatological skin impairments, sodium lauryl sulfate test was applied, and in vivo measuring of the biophysical parameters (erythema index, skin capacitance and the pH of the skin) in the artificially irritated skin was performed. As traditionally olive and sunflower oil have been used equally for extracts production, the experiment was carried out to investigate whether any of the oil extractants has the advantage over the other, and if the method of extraction might influence the desired activity. The observed activity has been connected to the chemical profile of the investigated extracts and their antioxidative properties. Materials and methods: In vivo measurements were performed using the appropriate probes for measuring skin capacitance, pH of the skin and erythema index (EI). The designed experiment enabled the evaluation of the anti-inflammatory effects of a seven-day application of oil yarrow extracts known in traditional medicine, on artificially irritated skin of volunteers. The chemical profile for the investigated samples was achieved applying the HPLC and UHPLC-MS methods. Also, ferric reducing antioxidant power (FRAP) test was performed to assess the antioxidant properties of the investigated samples. Results: The application of tested oil extracts on artificially irritated skin in vivo demonstrated the ability to re-establish their optimal pH and hydration of skin to the values measured prior to the irritation. Considering the EI transition, the investigated samples succeeded in re-establishing the baseline values, with no significant difference after three- and seven-day application. Conclusions: The data obtained in the study showed that the oil yarrow extracts had an evident anti-inflammatory property. Namely, the investigated extracts demonstrated significant anti-inflammatory effect in an in vivo double blind randomized study, using a sodium lauryl sulfate test. The skin parameters assessed in the study (skin capacitance, pH and EI) were restored to the basal values after three- and seven-day treatment with the tested extracts. The shown effects were attributed to yarrow oil extracts composition. The yarrow oil extracts might be used as promising base in the phytopreparations designed for dermatological application as anti-inflammatory agents with a positive impact on the skin pH and its moisture content. Graphical abstract: